The Kingfisher Children's Encyclopedia - Jennifer Justice (New York Kingfisher, 1998)
Presents more than 400 brief, alphabetically arranged entries on a variety of topics.
[editorial director] Jennifer Justice
Includes index. col. ill.
Keywords: Encyclopedias (3GdehShYGJs; Children's encyclopedias and dictionaries; General; Encyclopedias and dictionaries